PENGARUH COUNTRY OF ORIGIN, PERCEIVED QUALITY DAN PRICE TERHADAP PURCHASE INTENTION DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING (Studi kasus pada pengguna Oli Castrol di Bengkel Castrol Active Sawojajar Kota Malang) - M Faris efendi; N. Rachma; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to find out and analyze the Effects of Country of Origin, Perceived Quality and Price on Purchase Intention with Brand Image as Intervening Variables (case studies on Castrol oil users in Castrol Active Sawojajar Workshop, Malang City). Castrol oil sales in workshops have decreased so author as interested in doing this research. With existin theory hopefully it can answer the existing problems. The sample in this study were 72 customers. Based on the results of hypothesis testing it is known that the Country of Origin Perception, Perceived Quality, and Price have a direct influence on Brand Image. Country of Origin Perception, Perceived Quality, and Price have direct influence on Purchase Intention. Brand Image has a direct influence on Purchase Intention. The Country of Origin Perception, Perceived Quality, and Price have an indirect influence on Purchase Intention through Brand image as an Intervening Variable. Keywords: Country Of Origin, Perceived Quality , Price, Purchase Intention Dan Brand Image